Processing and microstructure of a fluorite high-entropy oxide (Zr0.2Ce0.2Hf0.2Y0.2Al0.2)O2-δ. Issue 2 (15th January 2022) - Wen, Yubin; Liu, Yufu
Abstract: Typical high-entropy fluorite oxides with five metal cations have exhibited improved thermomechanical properties. In this work, we have successfully prepared single-phase high-entropy (Zr0.2 Ce0.2 Hf0.2 Y0.2 Al0.2 )O2-δ fluorite oxides through the combination of sol-gel method and calcination, using metal nitrate/chloride, citric acid and absolute ethanol as the primary raw materials. A series of characterizations were employed for chemical, morphological and structural analysis of the calcined products. The five cationic elements were shown to be uniformly distributed in the nearly pure fluorite oxide without apparent segregation at the micro/nano-meter scales after 1500 °C calcination. Annealing and water quenching within the test temperature range did not witness any appreciable phase transition. It is revealed that the concentration of Ce 3+ in Ce ions reaches 33.84% and δ is equal to 0.234, yielding a nominal composition of (Zr0.2 Ce0.2 Hf0.2 Y0.2 Al0.2 )O1.766 . Cation and anion configurational entropy were found to be 1.609 R and 0.722 R, respectively, where R is the ideal gas constant, for a sum of the total configurational entropy of 2.331 R in the high-entropy system. Line defects inside the crystals and 3 types of crystalline boundary structures have been observed and identified among the mostly atomically sharp grain boundaries.